(untitled) (Research, Society and Development, 2021)
This study aims to identify the epidemiological profile and assess the occurrence of dizziness and the risk of falling in elderly people in the municipality of Serra Talhada, Pernambuco, Brazil. Therefore, a quantitative, descriptive and cross-sectional epidemiological study was carried out with elderly people complaining of dizziness and users of the Primary Care network of Serra Talhada, from August 2017 to August 2018. Questionnaires were used on the epidemiological profile, history medical history and dizziness. The risk of falls was assessed using the Timed Up and Go (TUG) test with logistic regression of the dichotomized variable (presence or absence of dependence). 101 individuals were evaluated, predominantly female, brown, with incomplete primary education, married, retired and sedentary. The average age was 71.1. The main comorbidities were Systemic Arterial Hypertension, visual impairment and arthritis. The TUG mean was 15.9 seconds, with no statistically significant relationship with gender, occurrence of dizziness, physical activity or self-perceived health. There was a direct relationship between dependence and age and the presence of diabetes mellitus, and an inverse relationship with the presence of SAH. It was found, through the analysis of the epidemiological profile and the identification of the variables that best contribute to the probabilistic occurrence of dependence according to the TUG criteria, inferring risk factors associated with the fall, allowing a quick and effective approach that could reduce the its occurrence.